2002
DOI: 10.1521/aeap.14.2.102.23901
|View full text |Cite
|
Sign up to set email alerts
|

Reasons For Not Using Condoms Among Female Sex Workers in Indonesia

Abstract: The aim of this study was to gather data on condom use among brothel-based female sex workers in Indonesia and to study the reasons for not using condoms in order to provide new and existing condom promotion programs with information to improve their performance. Quantitative data were gathered by KABP surveys (n = 1450) and a condom diary with a sample of 204 female sex workers. Qualitative data were collected by conducting focus group discussions and in-depth interviews among female sex workers and pimps. Ar… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

8
64
2
3

Year Published

2006
2006
2018
2018

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 82 publications
(78 citation statements)
references
References 12 publications
8
64
2
3
Order By: Relevance
“…Thus, there is a potential risk of infection through the sexual route for FSWs, especially through their regular clients and love mates, and from them to their other clients. This pattern of low condom use with regular clients and love mates was also observed in other studies among FSWs (Basuki et al, 2002;Le et al, 2000;Wong et al, 2003). In this study, we found that it was FSWs who were the ones who did not feel it was necessary to use condoms with regular clients and love mates.…”
Section: Discussionsupporting
confidence: 83%
See 1 more Smart Citation
“…Thus, there is a potential risk of infection through the sexual route for FSWs, especially through their regular clients and love mates, and from them to their other clients. This pattern of low condom use with regular clients and love mates was also observed in other studies among FSWs (Basuki et al, 2002;Le et al, 2000;Wong et al, 2003). In this study, we found that it was FSWs who were the ones who did not feel it was necessary to use condoms with regular clients and love mates.…”
Section: Discussionsupporting
confidence: 83%
“…The need for this knowledge is urgent, given that the epidemic is still largely confined within high-risk populations but has the potential to quickly spread to the general population. Although condom use by FSWs has been studied extensively in other parts of the world (Basuki et al, 2002;Ward et al, 2004;Larsen et al, 2004;Witte et al, 2000), little information is available on FSWs in Vietnam. In our previous qualitative study among FSWs in Hanoi (Tran et al, 2004), they reported higher condom use with irregular clients, although use was still low with regular clients and their love mates.…”
Section: Introductionmentioning
confidence: 99%
“…1,[7][8][9] This is the ''power of pleasure'' . Since condoms are generally perceived to reduce sexual pleasure, [10][11][12] it is vital for public health campaigns to address how to increase sexual pleasure when promoting condoms. There are many reasons why people choose not to use condoms, and instead practice riskier sex.…”
Section: 4mentioning
confidence: 99%
“…Because condoms are worn by men, and thus, because men may be the ones to actually experience physical discomfort such as erection problems and loss of sensation, [30][31][32][33] men may have more negative condom beliefs than women and differential correlates of negative condom beliefs could be found between men and women. To explore gender differences, the majority of analyses were conducted separately by gender.…”
Section: Introductionmentioning
confidence: 99%